2018
DOI: 10.1038/s12276-018-0118-x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of myeloid lineage cells is mapping out liver fibrosis post injury: a targetable lesion using Ketanserin

Abstract: Liver fibrosis is problematic after persistent injury. However, little is known about its response to an acute insult. Accumulation of myeloid lineage cells contributes into the promotion and resolution of inflammation and fibrosis. Using Cre-transgenic mice that specifically mark myeloid lineage cells with EYFP and burn as a model of acute systemic injury, we investigated the role of myeloid lineage cells in the liver after acute injury. Our data show that thermal injury in mice (30% total body surface area) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“… 25 This mechanism is mediated by adhesion molecules, chemoattractants, and cytokines. 26 The postoperative immunomodulatory effect of administrating pbMVs was compared with vehicle (saline-treated group) after a sham laparotomy surgery on POD4 (scheme 3). They were administered intragastrically twice on POD1 and daily for 3 days until POD4, while the control group received the vehicle alone.…”
Section: Resultsmentioning
confidence: 99%
“… 25 This mechanism is mediated by adhesion molecules, chemoattractants, and cytokines. 26 The postoperative immunomodulatory effect of administrating pbMVs was compared with vehicle (saline-treated group) after a sham laparotomy surgery on POD4 (scheme 3). They were administered intragastrically twice on POD1 and daily for 3 days until POD4, while the control group received the vehicle alone.…”
Section: Resultsmentioning
confidence: 99%
“…The regenerative role of serotonin has already been well-established in the liver (Lesurtel et al, 2006; Amini-Nik et al, 2018). The 5-HT1A receptor specifically has been identified as a key modulator in several other tissues, such as within the spinal motor neuron regeneration process in zebrafish (Barreiro-Iglesias et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this interplay has been documented in both directions where macrophages can enhance fibroblast migration (Dewor et al, 2007; Amini-Nik et al, 2014; Amini-Nik et al, 2018) as well. In normal tissue, the 5-HT1A receptor is also expressed in platelets, neutrophils, macrophages, and mast cells, all of which are components of the wound microenvironment (Shah and Amini-Nik, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It seems that 5-HTR 2B is more specifically targeted towards HSCs in the liver, while 5-HTR 2A, 2C, and 7 seem more closely associated with inflammation and oxidative stress damage in liver fibrosis. Saeid et al treated thermal-injured mice with a 5HTR 2A/2C antagonist (Ketanserin) and found that it could promote anti-fibrotic effects by regulating the phenotype of macrophages [ 77 ]. A study by Atallah et al showed that blocking 5-HTR 2A with Ketanserin or 5-HTR 7 with SB-269970 reduced oxidative stress/TGF-β1-induced liver fibrosis in CCl4-challenged rats [ 78 ], which were consistent with those reported by Dalia et al [ 79 ].…”
Section: -Ht In Cirrhosismentioning
confidence: 99%